Pobre ganancia ponderal en el neonato prematuro entre 30 y 34 semanas de edad gestacional y con muy bajo peso al nacer < 1500g como factor de riesgo para retinopatía de la prematuridad - Quispe Alejo, Elka Nataly (2019)
Retinopathy of prematurity (ROP) occurs in preterm infants (RNPT) who, because of their immaturity, are born with the incomplete retinal vascular system, which in the postnatal period experiences abnormal development. The pathogenesis of ROP is multifactorial, the most important risk factors are due to the immaturity of the RN: gestational age and low birth weight, nutritional factors and growth have also been described whose management can contribute to prevent its development among them. to the weight gain. ROP is one of the leading causes of childhood blindness in Third World countries; In a study that was carried out between 1998 and 2001 at the Institute of Child Health of Lima, it was reported that 44.9% of cases of childhood blindness were due to perinatal diseases. This high incidence is generally due to the lack of timely diagnosis and treatment due to the lack of adequate screening programs. In recent years, the development of postnatal weight has emerged as an important predictor of ROP, this study allows us to establish whether poor weight gain; practical and economic anthropometric measure, constitutes a preventable risk factor for the presentation of retinopathy of prematurity.